2019
DOI: 10.1177/0310057x18811746
|View full text |Cite
|
Sign up to set email alerts
|

The effect of guideline implementation on discharge analgesia prescribing (two years on)

Abstract: The provision of appropriate discharge analgesia can be challenging and is often prescribed by some of the most junior members of the medical team. Opioid abuse has been considered a growing public health crisis and physician overprescribing is a major contributor. In 2015 an initial audit of discharge analgesia at the Royal Perth Hospital led to the development of discharge analgesia guidelines. Compliance with these guidelines was assessed by a follow-up audit in 2016, which showed improved practice. This au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Educating junior hospital doctors and hospital pharmacists improved discharge opioid prescribing in terms of reducing the numbers of opioids prescribed, particularly slow release opioids, and improving the frequency of providing de‐prescribing recommendations for GPs. These findings are in line with those of a number of studies that found similar programs to be beneficial 7,15 . The principles of opioid stewardship should therefore be promoted and applied in all Australian hospitals; currently, there are still significant shortcomings in achieving this goal 16 …”
supporting
confidence: 86%
See 1 more Smart Citation
“…Educating junior hospital doctors and hospital pharmacists improved discharge opioid prescribing in terms of reducing the numbers of opioids prescribed, particularly slow release opioids, and improving the frequency of providing de‐prescribing recommendations for GPs. These findings are in line with those of a number of studies that found similar programs to be beneficial 7,15 . The principles of opioid stewardship should therefore be promoted and applied in all Australian hospitals; currently, there are still significant shortcomings in achieving this goal 16 …”
supporting
confidence: 86%
“…The underlying principles of opioid stewardship are the identification of risk factors for misuse, the assessment of analgesia requirements, the provision of appropriate but limited amounts of discharge opioids, and communication with the patient and, importantly, their general practitioner. The overall process should be governed by a hospital opioid discharge policy or guideline 7 …”
mentioning
confidence: 99%
“…7,8 Whilst the factors relevant in the United States do not necessary apply directly to Australia and New Zealand, suboptimal opioid handling has been demonstrated in our region. 9,10 Local measures are being developed at a national regulatory level, 11 and also at the individual health service or state level. 12, 13 However, current stewardship measures relating to prescribed opioids after surgical care across our region are unknown, and likely highly variable.…”
Section: Introductionmentioning
confidence: 99%
“…For these participants, the reality of self‐management in the early post‐discharge period was different to what they had expected. Providing greater information on safe opioid use and weaning advice could negate the risk of complications associated with unsafe opioid self‐management (Bartels et al., 2016; Feinberg et al., 2018; del Portal et al., 2016; Stewart et al., 2019).…”
Section: Discussionmentioning
confidence: 99%